Monitoring Postpartum Plasma Minerals Profile (Ca, P And Mg) And Fertility Without And With Estrus Synchronization Therapies At Day 90 In Suckled Anestrous/Subestrous Kankrej Cows - Naikoo, Mehrajuddin; Dhami, A.J.; Ramakrishnan, Ammu; Parmar , B.C.; Divekar , B.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was aimed at assessing the postpartum ovarian activity through clinical monitoring and plasma macro-minerals profile at 10 days intervals from calving till 140 days postpartum and fertility following various estrus synchronization therapies viz. Ovsynch, CIDR, Ovsynch + CIDR, Cosynch and PGF2α around day 90-95 postpartum in 30 suckled anestrous/ subestrous (6/treatment) Kankrej cows of an organized farm. Six normal cyclic cows were kept as control. The variations between 10 days interval were significant in some of the groups for mean values of plasma calcium (CIDR & Control), phosphorus (Ovsynch, Ovsynch + CIDR & Control) and magnesium (PGF2α & Control) studied from calving till 90 days postpartum. Estimations of plasma minerals were also done on day 0, 7, 9/10 (AI) and then at 10 days interval up to day 40 post AI following use of above estrus synchronization treatments. None of the protocols used, viz, Ovsynch, CIDR, Ovsynch + CIDR, Cosynch and PGF2α significantly influenced the plasma calcium, phosphorus and/or magnesium concentrations, though the estrus response (66.66, 83.33, 50.00, 66.66 and 66.66 %) and conception rate at induced estrus (16.66, 33.33, 16.66, 50.00 and 50.00 %, respectively) and overall of 3 cycles (33.33, 50.00, 33.33, 50.00 and 50.00 %) varied between them. The first service and overall 3 cycles conception rates in normal cyclic control group were 33.33 and 50.00 %, respectively. Among the conceived and non-conceived groups of Kankrej cows, the values of calcium and phosphorus varied insignificantly between intervals from day of calving to day 140 postpartum (10-40 post-AI), except for calcium in non-conceived group, and magnesium varied significantly between days in both conceived and non-conceived groups. The levels however did not vary between conceived and non-conceived groups at any of the intervals postpartum/post AI. It was concluded that neither the levels of plasma calcium, inorganic phosphorus and magnesium were good indicators of normal or abnormal reproductive status, nor they were influenced by different estrus induction protocols used in Kankrej cows, and that CIDR, Cosynch and PGF2α protocols were better in terms of estrus induction response and conception rate in anestrous/ subestrous zebu cows.
Keywords: Postpartum; Kankrej cows; Macro-minerals; Anestrous; Subestrous; Estrus Synchronization protocols